Improving Problem-Solving and Mathematical Self-Efficacy through the SSCS Model Based on Local Wisdom in Elementary School - Yunizal, Hayatul Fitri; Fadhilaturrahmi, Fadhilaturrahmi; Fauziddin, Moh.; Marta, Rusdial; Pebriana, Putri Hana (Journal of Education Research, 2024)
This research aims to improve problem solving abilities and mathematical self-efficacy with volume material and spatial meshes using the SSCS (Search, Solve, Create and Share) model based on local wisdom. This research is Classroom Action Research (PTK) which was carried out in 2 cycles, each cycle being held in 2 meetings. This research instrument consists of test sheets, teacher observations, student observations, questionnaires and documentation. Meanwhile, the data analysis techniques used are qualitative analysis and quantitative analysis. Based on the research results, it can be concluded that the SSCS (Search, Solve, Create and Share) model based on local wisdom can improve students' problem-solving abilities and mathematical self-efficacy in the material of volume and building nets in class V UPT SDN 014 Kumantan.